Changes in praxis of regulating access of some Siberian reindeer herders to the natural resources - Donahoe, Brian; Istomin, Kirill V. (The New Research of Tuva, 2010)
Praxis of land tenure and legislation of land use at reindeer herders and hunters is flexible and labile: they continuously adapt to the changing conditions of ecologic and social environment. Thus studies of transforms of those praxes affected by ecologic and social factors are of a special interest.Article has first been printed in yearly issue of "Races and people” in 2007, No. 33. It is being reprinted in our magazine by a kind permission of an executive editor of the annals D.A. Funk.
Keywords: traditional farmstead; land tenure; reindeer breeding; hunting; transforms; praxes; Siberia; Tofalars; Todzha Tuvans; Nenets people; comparative study